Switching Attention Within Working Memory is Reflected in the P3a Component of the Human Event-Related Brain Potential - Berti, Stefan (Frontiers in Human Neuroscience, 2016)
The flexible access to information in working memory is crucial for adaptive behavior. It is assumed that this is realized by switching the focus of attention within working memory. Switching of attention is mirrored in the P3a component of the human event-related brain potential (ERP) and it has been argued that the processes reflected by the P3a are also relevant for selecting information within working memory. The aim of the present study was to further evaluate whether the P3a mirrors genuine switching of attention within working memory by applying an object switching task: Participants updated a memory list of four digits either by replacing one item with another digit or by processing the stored digit. ERPs were computed separately for two types of trials: (1) trials in which an object was repeated and (2) trials in which a switch to a new object was required in order to perform the task. Object switch trials showed increased response times compared with repetition trials in both task conditions. In addition, switching costs were increased in the processing compared with the replacement condition. Pronounced P3a’s were obtained in switching trials but there were no difference between the two updating tasks (replacement or processing). These results were qualified by the finding that the magnitude of the visual location shift also affects the ERPs in the P3a time window. Taken together, the present pattern of results suggest that the P3a reflects an initial process of selecting information in working memory but not the memory updating itself.